2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort. (June 2023) - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter A.; Beckmann, Matthias W.; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther H.; Buchholz, Verena N.; Kornhuber, Johannes; Lenz, Bernd
Abstract: Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents ( M  = 13.32 years, SD  = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans ( M  = 7.87 years, SD  = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner. Highlights: Prenatal factors can influence child neurodevelopment through foetal programming. The 2D:4D is a biomarker for intrauterine androgen load and knowledge of 2D:4D's metric properties is essential. The 2D:4D proved to be an inter-individually stable measure with an intra-individual increase from childhood to adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the 2D:4D validity. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.